2006
DOI: 10.1096/fj.05-4728fje
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of natural hepatitis C virus with human scavenger receptor SR‐BI/Cla1 is mediated by ApoB‐containing lipoproteins

Abstract: The possible role of candidate receptors in the cellular penetration of HCV from serum of infected patients remains unclear. SR-BI/Cla1 interacts with plasma HDL, native and modified LDL, and VLDL, and facilitates cellular cholesterol efflux to lipoprotein acceptors. SR-BI/Cla1 binds HCV E2 protein and interacts with HCV pseudotypes via the HVR1 of the E2 envelope glycoprotein. Our data reveal that functional SR-BI/Cla1 expressed on the surface of CHO cells mediates the binding and uptake of HCV from the sera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 44 publications
4
133
1
4
Order By: Relevance
“…Thus, increasing the SR-BI expression level would improve binding of low density HCVfrg populations. This assumption is congruent with a previous demonstration that the interaction between serum-derived HCV and SR-BI was competed out by VLDL (59). Alternatively, SR-BI overexpression may prevent, at least partially, binding of viral particles to LDL receptor, which has been demonstrated to be a receptor conducive to a "non-productive" infection (60).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, increasing the SR-BI expression level would improve binding of low density HCVfrg populations. This assumption is congruent with a previous demonstration that the interaction between serum-derived HCV and SR-BI was competed out by VLDL (59). Alternatively, SR-BI overexpression may prevent, at least partially, binding of viral particles to LDL receptor, which has been demonstrated to be a receptor conducive to a "non-productive" infection (60).…”
Section: Discussionsupporting
confidence: 89%
“…Overall, our data are in agreement with a previous study indicating that the cellular uptake of HCV particles derived from the plasma of HCV-infected patients can be mediated by SR-BI through its interaction with lipoprotein components harbored by the virus (28). Although there may be differences between HCVcc and patient-derived particles, e.g.…”
Section: Journal Of Biological Chemistrysupporting
confidence: 93%
“…Altogether, these results indicated that HCV E2 is not at play for HCVcc attachment to SR-BI, which thus involves alternative virus surface component(s). Previous studies have underscored the association of HCV particles with ␤-lipoprotein components such as apoB, apoC-I, or apoE (17,22,28), which may contribute to HCV/SR-BI interaction. Importantly, no attachment of HCVcc particles occurred to cells expressing the M158R-mutated mouse SR-BI (Fig.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, apoB-containing lipoproteins (27) or high density lipoprotein (HDL) (28) appear to facilitate the interaction of HCV pseudoparticles or cell culture-grown HCV with scavenger receptor class B type I (SR-BI) (29). The exchangeable apolipoprotein apoCI, which is predominantly present in HDL, seems to interact with HCV particles via hypervariable region 1 (HVR1) in the N terminus of E2 thus promoting interaction and fusion of the HCV envelope with cellular membranes (30,31).…”
Section: Flagmentioning
confidence: 99%